Review of literature and case report of spermatic cord dedifferentiated liposarcoma - Nadeem, Muhammad Sohaib; Aqsa Jadoon (Journal of the Pakistan Medical Association, 2024)
Spermatic cord malignancies are a scarce modality and liposarcoma of spermatic cord is even a rarer condition encountered. Liposarcoma is usually a slowly progressive, non-tender, well circumscribed mass of variable shapes owing to conformity to fascial compartments. We are reporting a case of 65-year-old male, with a two-month history of initially tender and later non-tender mass in the scrotum, above the testis. Ultrasonography showed a right mid inguinal mass measuring 6x3x3 cm at the superior pole of the right testis and small fluid around the right testis. Fine needle aspiration cytology (FNAC) of the right inguinal mass revealed a spindle cell neoplasm. The patient underwent right inguinal radical orchiectomy with local wide excision of the sarcoma of the spermatic cord origin. Final histopathology confirmed dedifferentiated liposarcoma. No adjuvant treatment was offered and the patient was put on surveillance. —Continue